On the Trail of the First Interpreters in Early British Colonial Trinidad: An Exploration of Relevant Historical Aspects - Hoyte-West, Antony (Vertimo studijos, 2023)
With practitioners becoming increasingly of interest to translation historians, this study explores the presence of translators and interpreters in the sociocultural milieu of early British-ruled Trinidad. As an erstwhile Spanish colony with a significant Francophone influence, early 1800s Trinidad was a multilingual entity. The selected case studies track the presence of translators and interpreters at two key contemporary events: the Capitulation of 1797, which established British rule over the island, and the famous 1806 London-based torture trial of the island’s first British governor, Sir Thomas Picton. Adopting a postcolonial lens, the information presented is based on the examination of relevant early nineteenth-century sources. Noting the understudied nature of this geographical area and historical era, the insights outlined in this exploratory study aim to provide a useful starting point for further discussions of the ideological context surrounding translators and interpreters in multilingual colonial Trinidad.